Uso de ultrassom na hidrólise enzimática do óleo de crambe utilizando a lipase Lecitase Ultra (Fosfolipase A1) - Molinari, Deise (2015)
Fuels in Brazil have been produced in large scales, creating jobs and promoting economic growth and energy security. Biodiesel is an alternative fuel to petroleum diesel, made from renewable sources such as vegetable oils and animal fats which react with an alcohol in the presence of catalysts. The hidroesterificação is one of the biodiesel production routes and has been much studied, consisting of a hydrolysis step followed by esterification. These reactions when carried out using heterogeneous catalysts, require high temperatures and pressures to occur, which can be circumvented with the use of enzymes as a catalyst, which use milder conditions. The crambe is an oil that has favorable agronomic conditions and a major source of non-edible oil. The use of ultrasound has been shown to be effective in increasing enzyme activity and the formation of microemulsion. This work was comoobjetivo investigate the enzymatic hydrolysis reaction of crambe oil, aiming at the production of free fatty acids, using the Ultra Lecitase lipase (Phospholipase A1), batch reactor with orbital shaking and assisted a batch reactor with cavitaçãoultrassônica gavage. The conversions obtained using the ultrasound probe were lower than those obtained by the batch reactor with orbital shaker. In this study a central rotational design planning compound (CCRD) 2³ full was used to study the effects of varying temperature, fraction of water / oil (W / O) fraction and enzyme / substrate (E / S, where S = weight Total oil and water), the yield of the reaction was followed from acid analysis. The results of the planning for the ultrasound showed that the optimum conditions were met in the study limits. Showing that the use of the ultrasound probe is superior to conventional methods, significantly larger and better formed emulsions. With only 4 hours of reaction the yield of fatty acids was 57.7% at 40 ° C, thus decreasing the reaction kinetics, while the orbital shaker for yield was 65.36%, but 12 hours was required reaction at 50 ° C. Experiments were carried out in optimum condition to obtain the kinetics. A kinetic simplified mathematical model was used to describe reaction kinetics. The use of ultrasound despite providing lower conversion, proved to be a promising technique since it reduces the reaction time.